European Society for the Study of Tourette Syndrome 2022 criteria for clinical diagnosis of functional tic‐like behaviours: International consensus from experts in tic disorders. (13th January 2023) - Pringsheim, Tamara; Ganos, Christos; Nilles, Christelle; Cavanna, Andrea E.; Gilbert, Donald L.; Greenberg, Erica; Hartmann, Andreas; Hedderly, Tammy; Heyman, Isobel; Liang, Holan; Malaty, Irene; Malik, Osman; et al.
Abstract: Background and purpose: In 2020, health professionals witnessed a dramatic increase in referrals of young people with rapid onset of severe tic‐like behaviours. We assembled a working group to develop criteria for the clinical diagnosis of functional tic‐like behaviours (FTLBs) to help neurologists, pediatricians, psychiatrists, and psychologists recognize and diagnose this condition. Methods: We used a formal consensus development process, using a multiround, web‐based Delphi survey. The survey was based on an in‐person discussion at the European Society for the Study of Tourette Syndrome (ESSTS) meeting in Lausanne in June 2022. Members of an invited group with extensive clinical experience working with patients with Tourette syndrome and FTLBs discussed potential clinical criteria for diagnosis of FTLBs. An initial set of criteria were developed based on common clinical experiences and review of the literature on FTLBs and revised through iterative discussions, resulting in the survey items for voting. Results: In total, 24 members of the working group were invited to participate in the Delphi process. We propose that there are three major criteria and two minor criteria to support the clinical diagnosis of FTLBs. A clinically definite diagnosis of FTLBs can be confirmed by the presence of all three major criteria. A clinically probable diagnosis of FTLBs can be confirmed by the presence of two major criteria and one minor criterion. Conclusions: Distinguishing FTLBs from primary tics is important due to the distinct treatment paths required for these two conditions. A limitation of the ESSTS 2022 criteria is that they lack prospective testing of their sensitivity and specificity.